QUALITY OF LIFE IN PATIENTS WITH INVASIVE BLADDER CANCER AFTER RADICAL CYSTECTOMY AND URINARY DIVERSION (Modern American Journal of Medical and Health Sciences, 2025)
Background. Radical cystectomy remains the gold standard for the treatment of muscle-invasive bladder cancer (MIBC). However, the choice of urinary diversion has a significant impact not only on surgical outcomes but also on long-term quality of life (QoL).